Antiviral Potential of Eucalyptus Oil (Melaleuca cajuputi) as the Primary Protease Inhibitor of SARS-CoV-2 Revealed by Molecular Docking - Yuni Rahmayanti; Rizarullah Rizarullah; M Rizki Fakhrurrazi (International Journal Of Health Science, 2022)
The disease caused by the Corona Virus has afflicted hundreds of millions of individuals. The virus that causes the disease is SARS-CoV-2. To treat a variety of ailments, the Indonesian population favours the usage of medicinal herbs. The 1,8- cineol, karyophyllene, limonene, α-terpineol, α-pinene, dan β-pinene chemicals are present in eucalyptus oil (Melaleuca cajuputi) used in traditional medicine. This research was undertaken in silico to investigate the efficacy of these drugs as SARS-CoV-2 Main Protease (Mpro) inhibitors. The 1,8- cineol, karyophyllene, limonene, α-terpineol, α-pinene, dan β-pinene chemicals were molecularly docked using AutoDock Vina. Berdasarkan hasil molecular docking diperoleh Gibbs free energy (ΔG) dari kariofilen (-5.6 Kkal/mol), 1,8-cineole (-5.2 Kkal/mol), α-terpineol (-5.0 Kkal/mol), α-pinen (-4.9 Kkal/mol), β-pinen (-4.9 Kkal/mol), dan limonen (-4.8 Kkal/mol). Based on the results, the molecular docking data on these compounds likewise demonstrated no RMSD value greater than 2 Å. It indicates that the connection between the receptor and ligand is stable and that the response can occur spontaneously. The active site of the Mpro enzyme is the amino acid residue, where the interaction between the receptor and ligand occurs. Based on the bioactivity test, it can be inferred that the 1,8- cineol, karyophyllene, limonene, α-terpineol, α-pinene, dan β-pinene chemicals have varying bioactivities on different pharmacological targets. Because they satisfy Lipinski's requirements, these chemicals can also be utilized as oral medications. In addition, the toxicity test demonstrated that the test ligands exhibited minimal toxicity.